PENTINGNYA KOMUNIKSI ORGANISASI, MOTIVASI KERJA DAN KOMPENSASI UNTUK MENINGKATKAN KINERJA GURU - Dedy Kusumah Wijaya (MIX: JURNAL ILMIAH MANAJEMEN, 2015)
Abstract: The success of teachers in performing their duties also mean the institution's successin education. The purpose of this study was to determine the effect of organizationalcommunication, work motivation, compensation on the performance of teachers. This researchwas explanatory quantitative research method using correlation and regression model. Thisresearch at SMA Yuppentek 1 Tangerang involved 69 teachers as respondents. The resultsshowed that organizational communication, motivation and compensation partially andsimultaneously have significant effects on the performance of teachers. This research supportedthe previos reseraches.Keywords: Organizational Communication, Work Motivation, Compensation, TeacherPerformance.